Comparison of Development Mechanisms of Two Cyclones Affecting Northeast China - Gao Songying; Zhao Tingting; Song Lili; Meng Xin; Li Ruihan; Luo Jianyu; Zhang Xu; Pan Xiao (应用气象学报)
Two cyclones (C304 and C502) generated in the Jianghuai Basin on 3-5 March 2007 and 2-3 May 2016, affect the northeast region in a similar way. However, their intensities are different. The development of C304 is strong whereas that of C502 is explosive. Based on NCEP FNL analysis data and conventional data, their development dynamics are comparatively analyzed, through diagnosis of vorticity advection, temperature advection, moist potential vorticity and frontogenesis function, combining with the circulations of high and low altitudes. The result shows that the vorticity factor and thermal factor play roles in deepening cyclone development and guiding cyclone movement. There are strong cold and warm temperature advections at low attitudes in the process of the strong evolution of C304. High-level positive vorticity advection located above the ground cyclone provides high-level divergence field. During the explosive development of C502, cold and warm advections are inconspicuous. Highly positive vorticity advection is located in front of the high-attitude trough. The development of high-level closed circulation is promoted by the high-level positive vorticity advection. As for C304, strong frontogenesis and frontolyzes symmetrically develop on the lower troposphere, whereas the baroclinicity of C502 is inconspicuous. Positive moist potential vorticities strongly develop in the upper and lower troposphere unusually. C304 vorticity increases mainly in the lower troposphere, however, C502 vorticity increases mainly in the upper troposphere where the high-humidity vortex tongue develops drooping and merges with the troposphere below the positive wet-position vortex column. Two cyclones develop with coexistence of two high-level jets, non-latitude jet and the anticyclonic curved circulation. Southerly and northerly airflows are established in the background of the cyclonic circulation at 850 hPa. C304 is located on the left front of the southerly airstream, and C502 is located between the southerly and northerly airstreams. Under the effect of low-level intensity convergence and high-level intensity scattering, the vertical ascent motion of C304 increases in lower to upper middle troposphere above the ground cyclone center. Under the strong high-level intensity scattering and weak low-level convergence, the vertical ascent movement of C502 occurs on both sides of the ground cyclone center and middle troposphere. Low-level baroclinic forcing is the main starting development mechanism of C304, and high-level vortex downward transmission is the main mechanism of C502 development.